Children Well-Being Anak Usia Dini Dalam Perspektif Teoritis - Riana Khoerunisa; Taopik Rahman; Risbon Sianturi (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2026)
Children’s well-being is a crucial aspect in supporting the optimal of early childhood, particularly during the golden age, which represents a critical stage in a child’s life. However, various related to children’s well-being are still evident, including limited emotional support, less supportive environments, and inadequate parenting practices. This study aims to examine children’s well-being in early childhood form a theoretical perspective and to identify the factors influencing it. The research employs a literature review method by analizing relevant scientific journals and academic sources. The findings indicate that children’s well-being is a miltidimensional concept encompassing physical, emotional, social, and cognitive aspects. It is influenced by various factors, including family, educational environments, and social conditions. Theoretical perspectives such as attachment theory, developmental theory, and ecological theory emphasize that warm relationships and supportives environment play a vital role in enhancing children’s well-being, therefore collaboration among parent, and the wider community is essential to support the well-being of young children